Keterampilan Mengelola Kelas dan Implementasinya dalam Proses Pembelajaran - Sukatin; Nazifa, Aviq; Saputro, Muhammad Eko Agus; Efendi, Raihan Khan Nur; Maila, Yunis (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The diversity of students' backgrounds and learning abilities is the focus in managing the class. differences in abilities and tendencies that students have are related to students' learning attitudes, conditions like this are the most important part that must be considered because learning activities are largely determined by students' learning attitudes. When learning begins, students often show an attitude of rejection, meaning students are less able to respond to the learning carried out by the teacher. When students show an accepting attitude, it means that emotionally there is a willingness to accept learning carried out by the teacher. This reality requires the ability to manage the class well in order to create good learning conditions. creative, active, fun, happy and meaningful.